Analisis Pengaruh Investasi Pendanaan dan Dividen terhadap Nilai Perusahaan Makanan-Minuman di BEI 2019–2023 - Salman Alfarisi; Masriyanda Masriyanda; Silvi Reni Cusyana (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the influence of EPS, DER, and DPR on company value partially and simultaneously. The data used are secondary data in the form of financial reports obtained from the official website of the Indonesia Stock Exchange. The research method used is quantitative with purposive sampling technique, and data processing is carried out using Microsoft Excel and SPSS version 26. The research sample consists of 21 food and beverage sector companies. Data analysis is carried out through descriptive statistical tests, classical assumption tests, and hypothesis testing using multiple linear regression analysis models. The results of the study indicate that (1) the EPS variable has a negative and significant effect on company value, (2) the DER variable has an effect on company value, (3) the DPR variable has a negative effect on company value, and (4) the investment, funding, and dividend variables have a simultaneous effect on company value.